2015
DOI: 10.1080/1331677x.2015.1028245
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the audit committee on the internal audit operations in the system of corporate governance – evidence from Croatia

Abstract: The activities of the internal audit and audit committee in a company are of exceptional importance for the good practice of corporate governance. For the audit committee, performing numerous roles and responsibilities of are not possible without the appropriate interactions with the internal audit department. On the other hand, the quality of the internal audit operations in a company is largely determined by the cooperation with the audit committee. This research analyses the influence of the audit committee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
3
11
0
1
Order By: Relevance
“…The result is also in line with the findings of several prior studies which focused on the internal audit quality and governance (e.g. Sarens et al, 2012;Suyono & Hariyanto, 2012;Zaman and Sarens, 2013;Amin & Burki, 2014;Tušek, 2015;Drogalas, Arampatzis & Anagnostopoulou, 2016;Alzeban, 2020;Khalid, 2020).…”
Section: Hypotheses Testing Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The result is also in line with the findings of several prior studies which focused on the internal audit quality and governance (e.g. Sarens et al, 2012;Suyono & Hariyanto, 2012;Zaman and Sarens, 2013;Amin & Burki, 2014;Tušek, 2015;Drogalas, Arampatzis & Anagnostopoulou, 2016;Alzeban, 2020;Khalid, 2020).…”
Section: Hypotheses Testing Resultssupporting
confidence: 91%
“…Zaman and Sarens (2013) found that additional collaboration between the internal audit functions and audit committee in UK firms is positively impacted internal audit quality attributes. Similar result was found by Tušek (2015) in Croatia. Amin and Burki (2014) found that internal audit process and interaction with business managers have positively and significantly impacted corporate governance practices of Pakistani banks.…”
Section: Literature Reviewsupporting
confidence: 90%
See 2 more Smart Citations
“…In order AC to perform the roles and responsibilities, appropriate level of interactions with IAF is required. On the other hand, IAF's implication towards the reporting and audit quality is largely determined by the level of cooperation with the AC (Tusek, 2015). IAF budget is positively related to the hire of industry-specialist auditors and audit fee.…”
Section: Moderation Role Of Iafmentioning
confidence: 99%